Smarandache Curves according to Curves on a Spacelike Surface in Minkowski 3-Space R13. (16th October 2014) - Ozturk, Ufuk; Koc Ozturk, Esra Betul
Abstract : We introduce Smarandache curves according to the Lorentzian Darboux frame of a curve on spacelike surface in Minkowski 3-space R 1 3 . Also, we obtain the Sabban frame and the geodesic curvature of the Smarandache curves and give some characterizations on the curves when the curve α is an asymptotic curve or a principal curve. And we give an example to illustrate these curves.